Think like a mountain [videorecording] - Iluch, Julie; Sescon, Hesumaria
Tackles the plight of a tribal community in the upland. Focuses on the social and economic conditions of the people especially the problems on upland destructions of miners and loggers. A positive ecological attitude of farmers made a success on the sustainable agriculture.